Quantum Dots of [Na4 Cs6 PbBr4 ]8+ , Water Stable in Zeolite X, Luminesce Sharply in the Green - Kim, Joon Young (Advanced materials (Deerfield Beach, Fla.), 2020)
© 2020 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.